Morphological Attributes and Standardizing Plant Spacings with Harvesting Schedules to Enhance Growth and Yield of Stevia rebaudiana Bertoni - Shivani; Dutt, B.; Kumar, S.; Soni, K. (International Journal of Economic Plants, 2025)
A Field experiment was carried out to study morphological attributes and standardizing plant spacings and harvesting schedules to enhance the growth and yield of Stevia rebaudiana in the experimental field as well as in laboratory of the Department of Forest Products, College of Forestry, Dr Y S Parmar University of Horticulture and Forestry, Nauni, Solan,Himachal Pradesh (173230), India, from March, 2019- November, 2019. The experiment was conducted under Randomized Block Design (Factorial) with three replications, four spacing i.e. S1 (45–30 cm2), S2 (45-45 cm2), S3 (60-45 cm2), S4 (60–60 cm2) and two harvesting schedules i.e. H1: 50–60 days after transplanting, H2: 70–80 days after first harvesting. The narrow plant spacing S1 (45–30 cm2) gave maximum total fresh leaf yield (73.33 q ha-1), total dry leaf yield (30.07 q ha-1), total fresh foliage yield (130.53 q ha-1), total dry foliage yield (54.45 q ha-1) and B:C ratio (1.22) as compared to other spacingsin two harvests. Narrow spacing (45-30 cm2) can be recommended for planting of Stevia rebaudiana in order to get better yield and B:C ratio.